Pertobatan Ekologis Dalam Bingkai Filosofi “Sangserekan Bane’” Dan Pandemi Covid 19 - Teny Manopo (Institut Agama Kristen Negeri Toraja, 2021)
Abstract: Pandemic is a momentum that presents ecological reflection, forcing people to return to basic lessons about life and reflect on reconstructing new relations with the natural environment, which is closely related to the philosophy of